2019
DOI: 10.3390/healthcare7040128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decontamination Treatments on Micro-Shear Bond Strength between Blood–Saliva-Contaminated Post-Etched Dentin Substrate and Composite Resin

Abstract: Blood–saliva contamination negatively affects the bonding potential of adhesive agents. The study aimed to assess the effect of various cleaning protocols on micro-shear bond strength (μSBS) between blood–saliva-contaminated post-etched dentin and composite resin in total-etch and self-etch adhesives. The cleaning methods tested were water rinsing, 37.5% phosphoric acid (H3PO4) re-etching, 6% sodium hypochlorite (NaoCl), 2% chlorhexidine gluconate (CXG), isopropyl alcohol (IPA), and pumice. Nono-hybrid composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The increase in bond strength may be related to the ability of the adhesives to penetrate micro-spaces created by acid etching, i.e., the high diffusion coefficient of monomers. 16 Furthermore, the composition of adhesives seems to be particularly suitable for the bonding to contaminated enamel. Due to the hydrophilic nature of adhesives, they can remove saliva/blood (moisture) from the enamel surface, which allows infiltration of the hydrophilic monomer in the enamel pores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in bond strength may be related to the ability of the adhesives to penetrate micro-spaces created by acid etching, i.e., the high diffusion coefficient of monomers. 16 Furthermore, the composition of adhesives seems to be particularly suitable for the bonding to contaminated enamel. Due to the hydrophilic nature of adhesives, they can remove saliva/blood (moisture) from the enamel surface, which allows infiltration of the hydrophilic monomer in the enamel pores.…”
Section: Resultsmentioning
confidence: 99%
“…8 Surprisingly, little attention has been paid by researchers to contamination with blood, so there is considerable heterogeneity regarding the type of blood used in contamination studies. While some have used drawn recently blood, 16 others use anticoagulated blood 17 or plasma, 14 while others do not specify the type of blood used in their publications. 18 Based on these clinical difficulties, studies have been developed and they have found that bond strength between the resin sealant and contaminated surface is drastically decreased, 19 which results in complete or partial displacement of sealant in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies done to date have reported variable results. Even few studies[ 4 5 ] have reported that the saliva contamination of dentin had no adverse effect on the bonding efficiency of one-bottle adhesive systems while others have shown that the saliva contamination of the dentin surface produced a significant decrease in the bond strength[ 6 7 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results are in accordance with many other studies that showed that contamination of the bonded surface after curing of the self-etch adhesive results in lower bond strength. [ 6 7 9 10 11 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation